Pengaruh Model Pembelajaran Somatic Auditory Visualization Intellectualy berbantuan Lingkungan Hidup terhadap Hasil Belajar IPA Siswa - Kadek Andre Indrawan (Universitas Pendidikan Ganesha, 2018)
This study aims to determine the significant difference to the results of science learning between fourth graders Elementary School Gugus Ir. Soekarno South Denpasar academic year 2016/2017 which was taught by using SAVI model of assisted living environment and fourth grade students of SD Gugus Ir. Soekarno South Denpasar academic year 2016/2017 which was taught by conventional learning. This type of research is quasi experiment (quasi experiment).. Student learning outcomes data obtained through the test, the test used is the usual double-choice test, after obtaining the data of students' science learning outcomes then analyzed by t-test. Based on the significant level of 5% and dk = 74 (n1 + n2-2 = 37 + 39 - 2 = 74) obtained by ttable of 2.00 while tcount 3.49 (tcount = 3.49> ttable = 2.00). The average grade of the experimental class is 74.05 and the control class is 67.48. Thus, there is a significant difference to the results of science learning between fourth graders Elementary School Gugus Ir. Soekarno South Denpasar academic year 2016/2017 which was taught by SAVI model of environment-assisted learning and fourth grade students of SD Gugus Ir. Soekarno South Denpasar academic year 2016/2017 which was taught by conventional learning.